ChemInform Abstract: Metal‐Free Synthesis of ortho‐CHO Diaryl Ethers by a Three‐Component Sequential Coupling. Issue 21 (May 2015) - Liu, Fangliang; Yang, Huameng; Hu, Xinquan; Jiang, Gaoxi
Abstract The coupling between ortho‐trimethylsilyl aryl triflates, N, N‐dimethylformamide and diaryliodonium salts tolerates various functional groups.